Inter-generational link of obesity in term and preterm births: role of maternal plasma acylcarnitines - Wang, Guoying; Sun, Qi; Liang, Liming; Clash, Clary; Zhang, Cuilin; Hong, Xiumei; Ji, Yuelong; Radovick, Sally; Pearson, Colleen; Bartell, Tami R.; Zuckerman, Barry; Cheng, Tina L.; et al. (International Journal of Obesity, 2019)
Background/objectives Acylcarnitines, intermediates of fatty acid oxidation, are known to be involved in obesity and insulin resistance. Since maternal prepregnancy overweight or obesity (OWO) is a recognized major risk factor for offspring OWO, we hypothesized that maternal plasma acylcarnitines may play a role in inter-generational OWO. Subjects/methods This study included 1402 mother–child pairs (1043 term, 359 preterm) recruited at birth from 1998–2013 and followed prospectively up to age 18 years at the Boston Medical Center. The primary outcomes were child OWO defined as BMI ≥ 85th percentile for age and sex. The primary exposures were maternal prepregnancy OWO defined as BMI ≥ 25 kg/m 2 and maternal acylcarnitine levels measured in plasma samples collected soon after delivery using liquid chromatography–tandem mass spectrometry (LC–MS) in a targeted manner. Results Approximately 40% of the children in this study were OWO by age 5. Maternal OWO had a significant association with childhood OWO, both in term and preterm births. β-hydroxybutyryl-carnitine (C4-OH) levels were significantly and positively associated with child OWO among term births after adjustment for potential confounders and multiple-comparisons. Children born to OWO mothers in the top tertile C4-OH levels were at the highest risk of OWO: OR = 3.78 (95%CI: 2.47, 5.79) as compared with those born to non-OWO mothers in the lowest tertile (P for interaction of maternal OWO and C4-OH = 0.035). In a four-way decomposition of mediation/interaction analysis, we estimated that C4-OH levels explained about 27% (se = 0.08) of inter-generational OWO risk ( P = 0.001). In contrast, these associations were not observed in preterm births. Conclusions In this U.S. urban low-income birth cohort, we provide further evidence of the inter-generational link of OWO and reveal the differential role of C4-OH in explaining the inter-generational obesity between term and preterm births. Further investigations are warranted to better understand and prevent the inter-generational transmission of OWO.